PERPUSTAKAAN DIGITAL SEBAGAI MEDIA PUBLIKASI HASIL PENELITIAN ARKEOLOGI - Priswanto, Hery (Berkala Arkeologi, 2007)
In order to realize the library as an Information Resources Center, the Balai Arkeologi Yogyakarta library with its collections has begun to improve with various efforts to create a web-based digital library. What is expected to be one of the media for publication and information on archaeological research documentation that has been produced by the Balai for the public.